Perlindungan Hukum Terhadap Pekerja PKWT Atas Pemutusan Hubungan Kerja Sepihak Sebelum Masa Kontrak Berakhir - Maharany, Chezia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted to analyze how the law protects PKWT workers who are laid off before their contracts end, using a normative legal approach and qualitative research methods. The research results show that legal protection for PKWT workers for unilateral layoffs before the contract period ends is regulated in Law Number 13 of 2003 concerning Employment and Government Regulation Number 35 of 2021 concerning Specific Time Work Agreements, Outsourcing, Working Time and Rest Time, and Work termination. PKWT workers who are laid off unilaterally when the contract period has not yet expired, the company MUST provide compensation money to the PKWT worker as much as the remaining contract period in the contract agreement. Or giving severance pay/compensation if the PKWT worker has extended his contract with the company, but in the middle of the new contract being implemented the company lays off the worker. PKWT workers who are laid off unilaterally can take legal action to obtain their rights. Legal remedies that can be taken are through Bipartite, Conciliation or mediation, and the Industrial Relations Court.